Structural and Functional Aspects of the Neurodevelopmental Gene NR2F1: From Animal Models to Human Pathology - Tocco, Chiara; Bertacchi, Michele; Studer, Michèle (Frontiers in Molecular Neuroscience, 2021)
The assembly and maturation of the mammalian brain results from an intricate cascade of highly coordinated developmental events, such as cell proliferation, migration and differentiation. Any impairments of this delicate multi-factorial process can lead to complex neurodevelopmental diseases, sharing common pathogenic mechanisms and molecular pathways leading to their multiple clinical signs. A recently described monogenic neurodevelopmental syndrome named Bosch-Boonstra-Schaaf Optic Atrophy Syndrome (BBSOAS) results from NR2F1 haploinsufficiency. The NR2F1 gene, coding for a transcriptional regulator belonging to the steroid/thyroid hormone receptor superfamily, is known to play key roles in several brain developmental processes, from proliferation and differentiation of neural progenitors to migration and identity acquisition of neocortical neurons. In a clinical context, the disruption of these cellular processes could underlie the pathogenesis of characteristic symptoms affecting BBSOAS patients, such as intellectual disability, visual impairment, epilepsy, and autistic traits. In this review, we will introduce NR2F1 structure, molecular functioning, and expression profile in the developing mouse brain. Then, we will focus on Nr2f1 several functions during neocortical development, from cortical areal lamination to maturation of network activity, hippocampal development governing learning behaviours, assembly of the visual system, and finally establishment of cortico-spinal descending tracts regulating motor execution. Whenever possible, we will link experimental findings in animal or cellular models to corresponding features of the human pathology. Finally, we will highlight some of the questions still pending on the diverse functions played by Nr2f1 during brain development, in order to propose future research directions. All in all, we believe that understanding BBSOAS mechanisms will contribute to further unveiling pathophysiological mechanisms shared by several neurodevelopmental disorders and eventually lead to effective treatment.